Next generation design of floating systems for coastal solar farms - Bi, Cheng (Nanyang Technological University, 2023)
Solar power systems are extensively constructed as the major source of renewable energy production to combat climate changes and global warming. Floating solar farms are increasingly being explored in land-scarce coastal cities since the ground-mounted solar farms are constrained by land requirement. A few floating solar farms have been constructed on reservoirs with no occurrence of excessive structural displacement due to mild wave conditions. Since the size of floating solar farms could be limited by the usable areas of reservoirs, the next generation of floating solar farms with large power generation capacity will naturally transit from inland reservoirs to coastal area. Due to the complex weather and loading environment in coastal areas, two research questions for floating solar farms remain whether its structural stability can be maintained under the action of strong surface waves, and whether the fluctuating displacement of the floating solar panels would significantly reduce the solar energy generation. The present study addresses these research questions by proposing effective protection measures to reduce the motion of floating solar farms under wave action, and developing a numerical model to simulate the power output of floating solar panels under various high wind and wave conditions. Vertical tensioned sheet barriers are considered as effective wave protection measures and they can be made of viscoelastic materials with internal energy dissipation. The surface wave interaction with single or double partially penetrated vertical viscoelastic barriers is investigated analytically without pre-assumption of the barrier dynamic behavior. Five hydroelastic regimes with varying tension from elastic plate to inelastic membrane are identified, and the viscoelastic behavior of barriers is represented by the Voigt model. It is found that the wave transmission decreases as barriers shift from plate-like to membrane-like and its material has higher viscosity. When barriers have penetrations less than 40% of water depth, the wave transmission becomes dominated by the diffraction through the gap. The performance of the wave barrier improves significantly by the presence of the second sheet even with a small penetration. Vertical tensioned viscoelastic barriers are further used to stabilize the compliant platforms of floating solar farms in coastal environments. Configurations of single-barrier-platform system and dual-poro-viscoelastic-barrier-platform system are investigated analytically under wave action. In the single-barrier-platform system, the barrier is installed in front of the platform, and significant reduction in platform displacement can be achieved when the barrier is in the membrane-like hydroelastic regime with relatively high rigidity and has a penetration more than 40% of water depth. The wave transmission is reduced by the internal dissipation properties of the barrier material. In the dual-poro-viscoelastic-barrier-platform system, the platform is enclosed by double barriers installed on its front and lee sides. The results show that a longer barrier at the incident front side of the platform yields better performance than equal length on both sides given the same total barrier dimension. An increase in the porosity of the barriers reduces the displacement and wave loading on the barriers, but leads a higher wave transmission and larger platform displacement at the same time. Experiments on wave interactions with submerged vertical tensioned barriers as well as a single-barrier-platform system were carried out to quantify the performance of the barrier(s) on wave attenuation and platform stabilization. The experimental results of the single barrier agree well with the analytical predictions based on the linear wave theory in terms of the reduction in the tensioning effect on wave transmission and reflection with decreased barrier length. Furthermore, when placing a tensioned barrier in front of the platform, the results show that a barrier with a draft of ~40% of the water depth can effectively reduce the platform displacement. Different lengths of the floating platform and separation distances between the barrier and platform do not have a significant effect on attenuating the incident waves. Experiments on a novel adaptive barrier-mooring system (ABMS) including perimeter pontoons, submerged barriers, clump weights, mooring lines and anchors were conducted to examine the adaptivity of ABMS to a large tidal range as well as its performance on platform stabilization under wave action. The results show that the ABMS can reduce the platform vertical displacement by up to 40% for shorter wave periods compared with the elastic mooring cable systems, and it can adapt to the water surface variation of up to 36% of water depth. Additional benefits of ABMS also include the cost-effectiveness with the use of common materials, no need for periodic tightening and evenly distributed mooring tension. In the application of barrier protection on floating platforms, the barrier material is one of the key considerations with high strength, corrosion resistance and low cost. Three materials, i.e. nonwoven geotextile, PA 6 and HDPE, are considered for the fabrication of barriers in the present study with measured viscoelastic properties. The total costs of barriers made of these materials are estimated. It is found that the HDPE barrier with a penetration of 40% of water depth shows the best performance on the wave attenuation especially when it has a thickness of 10 cm, compared to the other two materials, with less than 40% allowable wave transmission. HDPE barrier is a relatively economical protection measure compared to other floating breakwaters. Finally, the power output of a floating solar array is simulated under various high wind and wave conditions at three offshore locations. A model of system electrical behavior is developed considering the effects of temperature, humidity, wind speed and wave characteristics. The solar irradiation over the PV panels is calculated considering the dynamic change of their tilt angles along with the platform motion under wave action, and the operational temperature of the PV panels is estimated based on the heat transfer with the ambient water underneath. It is found that the solar power output would remain stable even under high wind and wave conditions since the relative change in solar power output is very small, which is an important consideration for the hybrid solar-wind farms to maximize the areal density for the renewable energy production. The optimal initial angle of the floating PV panels is also examined for the three offshore locations. Together, the feasibility of installing floating solar panels among wind turbines is validated, provided that structural safety has been properly accommodated.